Incidence and severity of white mold for soybean under different cultural practices and local meteorological conditions - Gustavo Castilho Beruski; André Belmont Pereira; David Souza Jaccoud-Filho; Felipe Fadel Sartori; Paulo Cesar Sentelhas (Bioscience Journal, 2015)
The Sclerotinia sclerotiorum (Lib.) de Bary fungus is a necrotrophic and polyphagous pathogen with soybean crop as one of its most important hosts. However in order to occur epidemics caused by such a pathogen it is necessary that the climatic conditions, mainly air temperature and relative humidity be favorable to the occurrence and development of the disease. The current research aimed to assess the incidence and severity of S. sclerotiorum in soybean plants grown in Arapoti, PR, Brazil, as a function of different plant populations, row spacing, and microclimate. The experiment was conducted in a naturally infested area. The experimental design adopted was a randomized block in a factorial combination with 4 row spacing (0.35, 0.45, 0.60, 0.75 m) and 4 plant populations (150, 200, 250; 300 thousand plants per hectare), totaling 16 treatments and 4 replications. Throughout the current study we performed 4 assessments of incidence and severity. Local climatic conditions were favorable for the incidence and severity of the pathogen. Mean air temperature, rainfall, relative humidity and leaf wetness duration, monitored during all experimental period, favored the development of the pathogen in the experimental field. Yield and 100 seed weight did not show fluctuations as a function of variations on the incidence and severity of white mold in soybean crop fields. Nevertheless, crop yield was higher under a reduced spacing, whereas the 100 seed weight showed the highest values under the lowest plant population treatment.